Genital Herpes In Pregnancy-A Literature Review - Berliani, Kristin Nadia; Kusumaningrum, Niken (Newinera Publisher, 2025)
The hospital is one of the institutions engaged in health services. The main indicator of the standard of a health facility and is a measure of the quality of service, low customer satisfaction will have an impact on the number of visits that will affect the profitability of health facilities. This study aims to determine the effect of quality and the dominant variables that affect service on patient satisfaction at the Haji-Medan Hospital in 2020. The quantitative research was conducted through an analytical survey research approach with a cross sectional study approach. Testing through logistic regression on the independent variables, namely; Reliability, Responsiveness, Assurance, Empathy and Tangible from the respondents' questionnaire data as many as 80 samples. The results showed that service quality had a significant effect on patient satisfaction from four variables, namely; reliability p value 0.020 (p < 0.05), responsiveness p value 0.038 (p < 0.05), empathy p value 0.000 (p < 0.05), p value tangible 0.001 (p < 0.05). Assurance variable, the quality of health services has no effect on patient satisfaction with a p value of 0.332 (p> 0.05). The dominant variable affecting patient satisfaction is the empathy variable. It is recommended to improve services from the aspect of assurance in order to increase patient confidence in getting services so that patients can feel satisfied with the services provided.